The darker side of travel : the theory and practice of dark tourism - Sharpley, Richard 1956- Hrsg; Stone, Philip R. (Aspects of tourism, 2009)
Over the last decade, the concept of dark tourism has attracted growing academic interest and media attention. Nevertheless, perspectives on and understanding of dark tourism remain varied and theoretically fragile whilst, to date, no single book has attempted to draw together the conceptual themes and debates surrounding dark tourism, to explore it within wider disciplinary contexts and to establish a more informed relationship between the theory and practice of dark tourism. This book meets the undoubted need for such a volume by providing a contemporary and comprehensive analysis of dark tourism.